Accessible virtual reality for library orientation: A user-centered approach for visually impaired learners in inclusive education - Yakannut Yensathit; Pakinee Ariya; Kannikar Intawong; Kitti Puritat (Social Sciences and Humanities Open)
Virtual Reality (VR) is increasingly applied in education, yet most systems remain inaccessible to visually impaired learners. This study addresses that gap by developing a user-centered VR platform to support library orientation for visually impaired university students. Conducted at a Thai university, the research employed a research and development methodology, combining quantitative and qualitative data collection through usability testing, satisfaction questionnaires, and semi-structured interviews. A digital twin of the university library was created using Unity and deployed on Meta Quest 2, incorporating assistive features such as spatial audio cues, adjustable text, customizable lighting and contrast, and alerts for grade separation. Eight visually impaired students participated in the evaluation. Quantitative results showed a moderate usability score (average SUS = 67.83), while qualitative feedback emphasized the value of adjustable text and audio cues, with suggestions for improved personalization of contrast settings and audio speed. The study demonstrates the feasibility of inclusive VR design and provides practical insights for supporting visually impaired students, offering guidance for educators, developers, and policymakers seeking to advance digital accessibility and equity in higher education.